Familial Nanophthalmos Presenting with Spontaneous Uveal Effusion Syndrome. (17th February 2020) - Bansal, Reema; Menia, Nitin Kumar; Gupta, Amod
ABSTRACT: Purpose : To report two unique cases of spontaneous uveal effusion syndrome (UES) from the same family. Methods : The patients included father (54 years old) and a daughter (23 years old). The father presented 7 years ago with bilateral exudative retinal detachment, nanophthalmic eyes (axial length 16.11 mm and 16.43 mm in right and left eyes, respectively) with hypermetropia, and a thickened sclera on MRI. The daughter presented with left eye peripheral exudative annular retinal detachment with bilateral nanophthalmos (axial length 20.7 mm and 20.33 mm, in right and left eyes, respectively), with MRI showing ciliochoroidal detachment, suprachoroidal effusion and mild thickening of the sclera in left eye. Results : The father underwent subscleral sclerectomy in the left eye that led to resolution of submacular fluid. Scleral biopsy confirmed the deposition of glycosaminoglycans on Alcian blue stain. The daughter was kept under observation, because of absence of any macular subretinal fluid, and counselled about the familial nature of the disease and possible need for future intervention. Conclusion : This is the first report of familial nanophthalmos presenting with spontaneous UES.